Differences in levels of control object skills among grade 1 ballet dancers, students with co-curricular and students without co-curricular - Abdullah, Borhannudin; Mohd Khalid, Hanis; Lokman, Nur Anati; Hamidi, Muhammad Noor Hizami (Human Resource Management Academic Research Society, 2018)
Purpose: The purpose of this study was to identify the differences between level of control of object skills of grade one ballet dancers, students who were actively involved in co-curricular activity and students who were not actively involved in co-curricular activity. Methods: A study was conducted in the form of ex-post facto studies involving a total of 90 students, male and female who lived in Klang and Seremban districts. Test of Gross Motor Development (TGMD–2) was carried out to determine the skill level of the student based on the six control object skills that has been determined. Data were obtained through video footage and raw skill transcript score by reference norm age equivalents control objects. Kruskal-wallis statistical analysis was used to analyze the differences in level of control object skill group study. Findings: The findings of this study shows that the group of students who were actively involved in co-curricular activities has the highest mean (M = 3.07, SD = 1.14) in the control object skills as compared to a group of students who were not actively involved in co-curricular activities (M = 2.73, SD = 0.98) and grade one ballet dancers (M = 2.00, SD = 0.00). Meanwhile, it was found that there are significant differences between the three groups of study with estimated significant of 0.00. Discussions: Study shows the progress of the student control object skills grade one ballet dancers, students who were actively involved in co-curricular and student without co-curricular involvement are inactive according to their chronological age.